[BOOK REVIEW] The International Legal Status and Protection of Environmentally-Displaced Persons: A European Perspective - Anisa Fauziah (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2018)
Hélène Ragheboom writes this book to address the debatable discussions regarding the protection of climate change and environmentally displacement from both International and European perspectives. This book aims to understand whether persons who are outside their states of origin and unable, or unwilling, to return due to severe degradation of their living environment in their states of origin could, or should, receive international protection in Europe. https://doi.org/10.22304/pjih.v5n3.a11